Hubungan Pengetahuan, Sikap dan Perilaku Ibu dalam Pemberian Imunisasi Hepatitis B 0-7 Hari di Kota Banjarmasin - Ahmad Rizani, Mohammad Hakimi, Djauhar Ismail (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Indonesia belongs to medium and high endemic country of hepatitis B (HB) with the prevalence as much as 8% - 20% of the population. The risk for the prevalence of chronic HB is much more higher among infants infected during birth 90%, among children of 1 – 5 years 30% - 60%, and among adults 2%-6%. If infants of 0-7 days old are given the first dosage of HB immunization, the prevalence of being HB chronic patients is 23% and if the first dosage is given when infants are one months old, the prevalence of being HB chronic patients is 40%. The coverage of HB immunization for infants of 0-7 days old at Banjarmasin Municipality in 2006 was only 41%.Objective: The study aimed to identify the relationship between knowledge, attitude, and behavior of mothers in giving HB immunization to infants of 0-7 days old at Banjarmasin Municipality.Method: The study was observational and used cross sectional design. Subject of the study were 170 mothers having infants of 0-12 months chosen using consecutive sampling technique at 5 health centers with different coverage of HB immunization of infant of 0-7 days old. Data analysis used chi square and logistic regression. Strength of relationship was calculated using prevalence ratio with CI 95%.Result: The result of bivariable analysis showed that there was relationship between behavior of mothers in giving 0-7 day HB in immunization and knowledge RP=1.61 (CI 95%=1.35-191), attitude RP=1.49 (CI95%= 1.22-1.62), education RP=1.56 (CI95%=1.24-1.96), occupation RP=1.44 (CI95%=1.01-2.05) and birth assistants RP=1.48 (CI95%=1.21-1.82). The result of multivariable analysis using logistic regression showed that only 2 variables, i.e. knowledge and education statistically had significant relationship with behavior of mothers in giving 0-7 day HB immunization.Conclusion: There was relationship between knowledge and education and behavior of mothers in giving 0-7 day HB immunization.Keywords: knowledge, attitude, behavior, hepatitis B